Exploring the impact of review valence, disease risk, and trust on patient choice based on online physician reviews. (December 2019) - Han, Xi; Qu, Jiabin; Zhang, Tingting
Highlights: Online physician review valence was positively related to physician selection. Negative online reviews had greater influence on physician selection than positive reviews. High-risk disease strengthened the influence of online review valence on physician selection. Trust in OPRs was positively/negatively related to physician selection in the case of positive/negative online reviews. Abstract: Consumers' growing reliance on the Internet as an information source for decision making has raised the need for more research into online physician reviews (OPRs). This study conducted scenario experiment to explore how online review valence (positive vs. negative reviews), disease risk (high vs. low risk) and trust impact health consumers' choices when they are exposed to a neighbor-recommended physician. The results suggested that online review valence was positively related to physician selection, and negative reviews had greater influence than did positive reviews. The disease risk also impacted consumers' physician selection. A high-risk disease strengthened the influence of online review valence on physician selection. Trust in OPRs was positively related to physician selection in the case of positive online reviews, whereas it was negatively related to physician selection in the case of negative online reviews. Limitations and future directions were discussed.